Stressed Out About Plasmodium falciparum Gametocytogenesis - Usui, Miho; Williamson, Kim C. (Frontiers in Cellular and Infection Microbiology, 2021)
Blocking malaria transmission is critical to malaria control programs, but remains a major challenge especially in endemic regions with high levels of asymptomatic infections. New strategies targeting the transmissible sexual stages of the parasite, called gametocytes, are needed. This review focuses on P. falciparum gametocytogenesis in vivo and in vitro. Highlighting advances made elucidating genes required for gametocyte production and identifying key questions that remain unanswered such as the factors and regulatory mechanisms that contribute to gametocyte induction, and the mechanism of sequestration. Tools available to begin to address these issues are also described to facilitate advances in our understanding of this important stage of the life cycle.